Quranic rules in contracts and financial actions and their impact on the individual and society - Murad Jabbar Saeed (Zanco Journal of Human Sciences, 2020)
The Holy Qur'an wants a Muslim to follow the rules of Allah and his constitution in acquiring funds and obtaining halal livelihood. Islam as a religion relies on individuals and considers them as a center of reform and change. One of the most important aspects that have a direct impact on the lives of individuals and communities is the financial aspect and its disposition. Moreover, Islam and its book (quran) straightforward with this aspect to work and earn money and livelihood based on these criteria and controls in all parts of economy process and during the whole life. Also, Islam Calls for reform inside the economic system through financial contracts and actions, and establishing it as an integral part of the universality of its blessed invitation for the sake of achieving comprehensive justice, investment, production, consumption, distribution and other financial and economic activities.Thus, the research explains the concept of controls and the importance of them, as it explains the Quranic controls in contracts and financial transactions, also it shows the effects of Quranic controls on contracts and financial actions on the individual and society. The research includes introduction and four axes and conclusion.The first axis: the definition of controls and indicate their importance.The second axis: Quranic controls in contracts and legitimate financial transactions.Third axis: Quranic controls in contracts and illegal financial transactions.Axis IV: Quranic controls and their impact on the individual and society in contracts and financial transactions.Finally, the most important outcomes are summarized in conclusion.